Effectiveness of Digital Mental Health Intervention in Middle Eastern Conflict Zones: (A Technology-Based Meta-analysis) - Nurzahara Sihombing; M. Agung Rahmadi; Sarah Atikah; Nanda Liana Lubis; Lisa Maharani Rizki; Helsa Nasution; Luthfiah Mawar; Rasil Hakim Hasibuan (Stikes Kesdam IV/Diponegoro Semarang, Indonesia, 2026)
This meta-analysis evaluates the effectiveness of digital mental health interventions in post-conflict regions of the Middle East by synthesizing findings from 47 studies (N = 8,427) published between 2015 and 2024. Using a random-effects model, the results demonstrate that digital interventions consistently produce significant reductions in symptoms of PTSD (g = 0.82, 95% CI [0.74, 0.90], p < .001), depression (g = 0.76, 95% CI [0.68, 0.84], p < .001), and anxiety (g = 0.71, 95% CI [0.63, 0.79], p < .001). Moderator analyses show that mobile application–based interventions (g = 0.88) outperform web-based platforms (g = 0.69). The optimal duration falls within the 8 to 12 week range (g = 0.85) with a retention rate of 76.4 percent. These findings confirm Maalouf et al.'s (2019) argument about the accessibility of digital technologies in conflict settings, yet indicate stronger effects for mobile interventions than those reported by Kamali et al. (2020). In contrast to the meta-analysis by Al Dweik et al. (2024), which examined general interventions, this study identifies the specific effectiveness of artificial intelligence–driven personalized treatment (g = 0.91) and encrypted peer-to-peer support (g = 0.87). The results reinforce that digital interventions can serve as a strategic alternative when conventional mental health services are difficult to access.